Contrasting structural styles in SW Dominican Republic as an evidence of strain partitioning in an island arc (Hispaniola)–continent (North America) oblique collisional setting - Hernaiz-Huerta, P. P.; Díaz de Neira, J. A.; García-Senz, J.; Lopera, E.; Escuder-Viruete, J.; Pérez-Estaún, A. (TRABAJOS DE GEOLOGÍA, 2009)
The contrasting structural styles observed in SW Dominican Republic are proposed as evidences for strain partitioning in an island arc-continent oblique collisional setting. The Peralta fold and thrust belt (formerly the back arc-basin) shows a relatively homogeneous pure shear controlled deformation. Thrusting and associated folding developed in the island arc basement corresponding to the Tireo formation is considered partly formed under the simple shear component that rules the deformation in the Median Belt, where left lateral strike-slip motion is well localized along discrete structures. The widespread and pervasive intense fracturing developed coevally to folding and high angle thrusts in Neiba, Martín García and Bahoruco Sierras (and the neighbouring Enriquillo basin), suggests regional scale E-W distributed subvertical shearing.